Ujaran Kebencian Terhadap Islam di YouTube di Indonesia Periode Januari-Juni 2021 - Mutiara Putri Riany; Nirwan Syafrin Manurung; Hilman Hakiem (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The phenomenon of hate speech against religions including Islam in Indonesia is a serious problem. One of the ways to spread hate speech against Islam is by using social media such as YouTube. This problem is already regulated in Law Number 11 of 2008 concerning ITE (Information and Electronic Transactions) in Article 28 Paragraphs 1 and 2 and Article 45A Paragraph 2. This study aims to observe the phenomenon of hate speech in general and hate speech against Islam in particular, on YouTube social media in Indonesia during the period January-June 2021. This study is qualitative in nature and based on library research. The study found that the phenomena of hate during the period under study, in general, increased. However, such an increase is not stable. It highly increases during the General Election season in 2019. During the period January-June 2021, the study at least three accounts which directly attacks Islam, namely, Muhammad Kece, Joseph Paul Zhang, and Saifuddin Ibrahim. The nature of hate speech against Islam carried out by those three accounts comes in the form of insulting, harassment, slander, provocation, and hoaxes. Islam prohibits hate speech and stipulates it as a criminal act with the category of ta'zir. The Indonesian government has also taken firm steps to eradicate hate speech on social media. However, this problem has not been resolved properly due to the difficulty of controlling the use of social media. Keywords: Hate Speech; Islam; YouTube